Factors Influencing the Teaching Intention of Business College Teachers to Fulfill Digital Entrepreneurship Courses - Yu, Tai-Kuei; Chao, Cheng-Min; Wang, YiJie (Frontiers in Psychology, 2022)
With the increasing promotion of entrepreneurship in Taiwan’s universities and the establishment of departments of innovation or entrepreneurship management, it has become an emerging trend to encourage college students to become entrepreneurs or participate in entrepreneurial competitions during their undergraduate years. The Internet has stimulated the development and widespread application of new business models and has created a large number of entrepreneurial opportunities. Universities engaged in digital entrepreneurship education over the past have hardly designed a curriculum to teach the content of digital entrepreneurship. This study integrated “task-technology fit,” “self-determination theory,” and “interactive participation,” into its investigation on the teaching intention of business college teachers to develop digital entrepreneurship courses. The sample size was 126 participants. Using partial least squares analysis, the research model represented high internal consistency and confirmed the good reliability of the scales. This study presented that three dimensions of the concept (teachers’ positive attitude emotions, task-technology fit, interactive participation) were highly prioritized in their intention to teach digital entrepreneurship courses. The coefficient of the endogenous variables was 0.503 for positive attitude emotions, 0.571 for task-technology fit, and 0.392 for teaching intention. Based on a quantitative survey on the teaching intention of business college teachers to fulfill digital entrepreneurship courses, this study demonstrated the implications of digital entrepreneurship education issues that are relevant to the role of teacher’s dimension from different viewpoints, and discussed the implications of teaching digital entrepreneurship courses for digital entrepreneurship practices and entrepreneurship education.